US Guidelines for immune tolerance induction in patients with haemophilia a and inhibitors. (2nd June 2015) - Valentino, L. A.; Kempton, C. L.; Kruse‐Jarres, R.; Mathew, P.; Meeks, S. L.; Reiss, U. M.; the International Immune Tolerance Induction Study Investigators
<x xml:space="preserve">Abstract</x> Introduction The development of anti‐factor VIII (FVIII) antibodies (inhibitors) is the most serious treatment‐related complication in patients with hemophilia A, rendering standard replacement therapy ineffective, heightening the risk for uncontrollable bleeding and morbidity, decreasing quality of life, and increasing healthcare costs. Aim Formulate evidence‐based guidelines for optimizing immune tolerance induction (ITI) in patients with hemophilia A and inhibitors. Methods Results from the International ITI study and other available evidence were used to develop guidelines for ITI. Results Predictors of ITI success were identified and recommendations made for ITI with regard to candidates, timing, product, regimen, monitoring, defining success, concurrent immunomodulation, duration of treatment, and bleed management before and during ITI. Conclusion Evidence‐based recommendations to guide treatment decisions may increase the likelihood of successful inhibitor eradication and the induction of FVIII tolerance in patients with hemophilia A who develop inhibitory antibodies.